An impedance-based pole-zero method for estimating complex material parameters of piezoceramic plates. (1st December 2022) - Cong, Shuai; James Hu, Sau-Lon; Li, Hua-Jun
Abstract: Precisely determining complex-valued elastic, piezoelectric, and dielectric parameters of piezoceramic plates has been a challenging problem. Given measured impedance functions (MIFs), this study develops a pole-zero finite element model updating (FEMU) method for determining sensitive complex material parameters (CMPs) associated with k 31 -mode and k 33 -mode piezoceramic plates. The proposed method includes two novel aspects: (a) extracting complex-valued poles and zeros, which are related to the eigenvalues of short- and open-circuit FE models, respectively, from MIFs, and (b) developing a sensitivity-based FEMU method to update the CMPs based on the measured poles and zeros. In the numerical studies, both computer simulations and lab experiments are carried out to demonstrate the excellent performance of the developed method.